2010
DOI: 10.1128/aem.01917-10
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Isobutene from 3-Hydroxy-3-Methylbutyrate by Diphosphomevalonate Decarboxylase

Abstract: Isobutene is an important commercial chemical used for the synthesis of butyl rubber, terephthalic acid, specialty chemicals, and a gasoline performance additive known as alkylate. Currently, isobutene is produced from petroleum and hence is nonrenewable. Here, we report that the Saccharomyces cerevisiae mevalonate diphosphate decarboxylase (ScMDD) can convert 3-hydroxy-3-methylbutyrate (3-HMB) to isobutene. Whole cells of Escherichia coli producing ScMDD with an N-terminal 6؋His tag (His 6 -ScMDD) formed isob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 33 publications
2
39
2
Order By: Relevance
“…Natural alkene sources are mainly emissions from hydrocarbon reservoirs and hydrothermal sites (11) as well as from burning and pyrolysis of organic materials (21,55). In addition, traces of isobutene could be produced from side reactions occurring in the metabolism of isovaleric acid and 3,3-HMB (14,15). Most important, of course, isobutene and isoamylene are also present in oil derivatives such as gasoline (24).…”
Section: Discussionmentioning
confidence: 99%
“…Natural alkene sources are mainly emissions from hydrocarbon reservoirs and hydrothermal sites (11) as well as from burning and pyrolysis of organic materials (21,55). In addition, traces of isobutene could be produced from side reactions occurring in the metabolism of isovaleric acid and 3,3-HMB (14,15). Most important, of course, isobutene and isoamylene are also present in oil derivatives such as gasoline (24).…”
Section: Discussionmentioning
confidence: 99%
“…However, higher alcohols, like isobutanol, possess several advantages, such as a lower hygroscopicity, vapor pressure, and corrosivity, full compatibility with existing engines and pipelines, and a higher energy density, allowing safer handling and more efficient use than ethanol (15). Furthermore, isobutanol can serve as a precursor for the production of isobutene (34), which nowadays is exclusively produced in large scale by petroleum refining and is used as a gasoline additive and for the production of butyl rubber and specialty chemicals (20).…”
mentioning
confidence: 99%
“…It has been shown that 3-hydroxyisovalerate can be converted to isobutene as a side-activity of mevalonate diphosphate decarboxylase (Figure 4). [62][63] Also, patent applications describe isobutanol dehydration as a side activity of engineered oleate hydratase and other hydratases. [48][49] Fermentative production of isobutanol is described in section 0.…”
Section: Isobutenementioning
confidence: 99%